Cellulases - Gilbert, H. J. (Methods in enzymology, 2012)
Cellulase refers to a class of enzymes produced chiefly by fungi, bacteria, and protozoans that catalyze cellulolysis. This volume in the Methods in Enzymology series comprehensively covers this topic.